Determinants affecting work-life balance among employees in Johor Petroleum Development Corporation Berhad (JPDC) / Siti Nabihah Zulkifle - Zulkifle, Siti Nabihah (Faculty of Business and Management, 2018)
This study examines on determinant affecting work-life balance as mean to enhance growth for the success of the organization and creating productive working environment. The research was conducted among the employees of Johor Petroleum Development Corporation Berhad (JPDC). Work-life balance is the big scope but the researcher only focus on the four determinants that affecting employee’s in JPDC are job engagement, organizational support, family support and emotional intelligence. Therefore, relationship between the independent variable would help the JPDC especially in Human Resource Department manage the conflict successfully. This paper prove that determinants affecting work-life balance would result positive impact to solve employees conflict with frequency analysis, reliability analysis, descriptive analysis, correlation analysis and regression analysis that have been conduct. The data has been analysed using Statistical Package Social software.